Pelaksanaan Perjanjian Kredit Angsuran Sistem fidusia (Kreasi) dengan Jaminan Fidusia pada PT. Pegadaian Larantuka Kabupaten Flores Timur - Ayu Wulandari; Siti Ramlah Usman; Helsina Fransiska Pello (Pemuliaan Keadilan, 2024)
Installment Credit with Fiduciary System at Pegadaian (Pawnshop) is quite popular among the public, especially for small and medium enterprises, as it provides easy and fast financing services. The purpose of this study is to understand the implementation of the Fiduciary System Installment Credit Agreement at PT. Pegadaian Larantuka. The theoretical benefit of this research is to provide information for the development of legal knowledge, particularly in the field of civil law regarding Fiduciary System Installment Credit at pawnshops, while the practical benefit is to contribute ideas and suggestions for relevant stakeholders, especially customers. The research method used is empirical research. The data used in this study are based on the relevance of the data sources, which include primary, secondary, and tertiary data. The results of the study indicate that the implementation of the fiduciary system installment credit agreement at PT. Pegadaian Larantuka is offered to individuals who have been running a business for at least one year. The process starts with the prospective customer applying for credit, followed by Pegadaian analyzing the applicant's profile. The prospective customer then completes the necessary requirements and signs an agreement form, binding both parties to a specific object. The factors hindering the proper implementation of the KREASI agreement are typically caused by the customer or debtor's default, which may result from financial issues, negligence, economic conditions, or other unforeseen circumstances.